2022
DOI: 10.1371/journal.pone.0269800
|View full text |Cite
|
Sign up to set email alerts
|

The use of social robots with children and young people on the autism spectrum: A systematic review and meta-analysis

Abstract: Background Robot-mediated interventions show promise in supporting the development of children on the autism spectrum. Objectives In this systematic review and meta-analysis, we summarize key features of available evidence on robot-interventions for children and young people on the autism spectrum aged up to 18 years old, as well as consider their efficacy for specific domains of learning. Data sources PubMed, Scopus, EBSCOhost, Google Scholar, Cochrane Library, ACM Digital Library, and IEEE Xplore. Grey l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 81 publications
(108 reference statements)
0
25
0
2
Order By: Relevance
“…Robotic therapy is still in its infancy, and its effectiveness has not been fully studied in regards with autism symptomatology or cognitive functions. Its advantages relate to the ability of the robot to take on various roles such as instructor, educator, social companion, entertainer, therapist's assistant, diagnostician and observer (Kouroupa et al, 2022 ). Important disadvantages at this stage are the inability to meet the therapists’ or the family’s expectations as well as difficulties related to cost, maintenance, programming, and safety (Alabdulkareem et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robotic therapy is still in its infancy, and its effectiveness has not been fully studied in regards with autism symptomatology or cognitive functions. Its advantages relate to the ability of the robot to take on various roles such as instructor, educator, social companion, entertainer, therapist's assistant, diagnostician and observer (Kouroupa et al, 2022 ). Important disadvantages at this stage are the inability to meet the therapists’ or the family’s expectations as well as difficulties related to cost, maintenance, programming, and safety (Alabdulkareem et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reviews of more than fifty studies using social robots concluded that they showed encouraging results on social behaviour, imitation and engagement (Begum et al, 2016 ; Papakostas et al, 2021 ; Yuan et al, 2021 ), but they were also lacking scientific rigor as they were mainly non-randomized with small samples and questionable methodology (Duradoni et al, 2021 ; Ismail et al, 2019 ). More specifically, at a recent meta-analysis (Kouroupa et al, 2022 ) it was found that the methodological quality of robot-assisted autism studies was affected by the absence of an intelligence assessment, the variety of the duration of the intervention (from 3 to 180 min), the variety of the session’s frequency (single session to 3 times a week), the lack of longitudinal data and the absence of clear documentation of statistical significance in some of the studies.…”
mentioning
confidence: 99%
“…Previous studies investigating the efficacy of robot‐assisted interventions often focused on subjective reports of therapists and parents, which might produce less reliable or generalizable results than clinical scales or behavioral data (DiPietro et al, 2019). In a recent meta‐analysis by Kouroupa et al (2022), the authors demonstrated that robot‐mediated interventions significantly improve social functioning, regardless of the specific measure applied to assess improvements in social cognition abilities. However, to provide reliable, replicable, and generalizable results, we resort to metrics for evaluating robot efficacy in the clinical environment that is in line with assessment tools used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…There are also similar efforts in the automated detection of verbal behavioral markers, such as peculiarities in prosody or idiosyncratic utterances ( 13 ), as well as in vocalizations ( 14 ) along with a number of increasingly studied but still nonspecific biomarkers ( 15 ). Additionally, an increasing number of studies has explored the use of digital interventions in autism, allowing for the assessment via meta-analyses [e.g., ( 16 18 )]. However, in the digital assessment of behavioral marker research, streamlining is lacking.…”
Section: Introductionmentioning
confidence: 99%